Teaching pelvic floor muscle training to local health workers in rural Nepal. Issue 6 (2nd November 2018) - Caagbay, Delena; Black, Kirsten; Wattimena, Jeany; Raynes-Greenow, Camille
ABSTRACT: Women in Nepal who suffer from pelvic floor disorders often have limited access to health advice. In rural areas, auxiliary nurse midwives (ANMs) are responsible for maternal health counselling and services. We sought to investigate whether an educational workshop on pelvic floor muscle training (PFMT) for ANMs would improve their knowledge and enable them to correctly teach PFMT to community women. We invited ANMs from three rural regions in Nepal to attend 1-day training workshops. Using a structured questionnaire we assessed pre- and post-PFMT knowledge following a workshop. Subsequently, three ANMs were observed teaching PFMT to women with varied levels of supervision. A correct pelvic floor muscle (PFM) contraction was assessed with transabdominal real-time ultrasound. The Wilcoxon signed rank paired test was used to assess the change in knowledge. In total, 88 ANMs attended the three training workshops. Following the workshop, the mean change in knowledge scores increased by 18.5% (95% confidence interval (CI): 15.5–21.6%, p  < 0.001). The three selected ANMs successfully taught 71%, 45% and 17% of the women to correctly contract their PFMs with greater supervision resulting in higher success. A workshop on PFMT significantly increased ANMs' knowledge, and they were able to successfully teach PFMT when given additional one-on-one supervision. Teaching ANMs about PFMT may be a worthwhile strategy to reach women in rural settings who experience pelvic floor disorders.